If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying a + -22 + 3a = 2 Reorder the terms: -22 + a + 3a = 2 Combine like terms: a + 3a = 4a -22 + 4a = 2 Solving -22 + 4a = 2 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '22' to each side of the equation. -22 + 22 + 4a = 2 + 22 Combine like terms: -22 + 22 = 0 0 + 4a = 2 + 22 4a = 2 + 22 Combine like terms: 2 + 22 = 24 4a = 24 Divide each side by '4'. a = 6 Simplifying a = 6
| 4x/(2x^2) | | 9m=10m-8 | | 9/10•15x/3 | | 3(z+5)+4=-12 | | e^5x+8=11 | | -0.8z=-12 | | 9/10•15χ/ | | -33+1.1z=-6.6 | | .25x=17.31 | | 0=y^2-8y-160 | | 0.12x+x=16000 | | -7x-6+8=50 | | 198/12 | | 7x-28=4x+47 | | 2(5x-4)-3(x+6)=5(x-1)-x | | 2x+4=4-3+3x+5 | | -2v+9=-7+2v | | 4x+13=6x-47 | | 10y=500 | | X-3(5)=11 | | 6c+1=2c+59 | | 5(2.1y+3)=36 | | -2+9=-7+2v | | 4y=18-(14y+16) | | 8+2r-4r=1-3r | | -2(0)+3y=-19 | | 8[8-k]=-2[k-5] | | 8=2q+-11 | | 7x-6=3(x+2)+10x | | D=Bak | | f(x)=2lx-1l+3 | | 5(x+8)=3x+9 |